La Fórmula de Barcan es equivalente al Teorema de Deducción - Cifuentes Vásquez, José Carlos (1992)
In this note we discuss a general form of the Deduction Theorem (DT) for first order modal systems, which permits to derive severa! other formulations of DT found in the literature, and their relationship with the Barcan's Formula